Laser-induced in-situ reduction metal bismuth nanocluster modified bismuth vanadate composite photo-anode as well as preparation method and application thereof
The precipitation of metal bismuth nanoclusters on the surface of bismuth vanadate was induced by laser-induced in situ reduction method, forming a bismuth vanadate composite photoanode modified by metal bismuth nanoclusters, solving the problem of slow reaction kinetics of bismuth vanadate photoanode and significantly improving the photocurrent density and charge separation efficiency.
Patent Information
- Application Number
- CN202411482232.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-11
AI Technical Summary
The separation efficiency of electron and hole pairs of bismuth vanadate photoanode is poor, resulting in slow reaction kinetics, hindering its practical application in solar energy conversion.
Through laser-induced in situ reduction method, the precipitation of metal bismuth nanoclusters is induced on the surface of bismuth vanadate to form a bismuth vanadate composite photoanode modified by metal bismuth nanoclusters.
It significantly improves the photocurrent density and charge separation efficiency, inhibits the recombination of electron-hole pairs, and improves the PEC water decomposition performance.
Smart Images

Figure CN119592999A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoelectrochemistry and the technical field of new energy material synthesis, and relates to a laser-induced in-situ reduced metal bismuth nanocluster modified bismuth vanadate composite photoanode, and a preparation method and application thereof. Background Art
[0002] With the rapid development of excessive population growth, social modernization and industrialization, the consumption of traditional fossil fuels has continued to increase, accompanied by the emergence of environmental pollution problems and the increasingly severe energy crisis. While meeting the demand for energy consumption, developing renewable energy to replace fossil fuels has become a major challenge. Hydrogen energy, as an environmentally friendly clean energy, has many advantages such as high energy density, abundant resources, wide sources, and diverse uses. Therefore, it is regarded as one of the ideal renewable energy sources. Therefore, there is an urgent need to develop efficient and green hydrogen production methods.
[0003] Solar energy is one of the most abundant natural resources. It is cheap and easy to use. Using effective methods to store and utilize solar energy and achieve efficient and economical solar catalytic conversion is a key technical issue that needs to be broken through. Photoelectrochemical (PEC) water splitting technology is one of the important ways to convert solar energy into chemical energy. The photoelectrocatalytic system realizes the spatial separation of oxidation and reduction reactions. The hydrogen and oxygen evolution reactions occur at the cathode and anode, respectively. It is an important way to utilize solar energy. The oxygen evolution reaction involves a four-electron process with a large reaction energy barrier and a high reaction overpotential, becoming the rate-controlling step of the overall water splitting reaction. Therefore, it is urgent to develop high-performance photoanodes to improve the overall water splitting reaction efficiency.
[0004] Bismuth vanadate (BiVO4) is one of the most promising materials for metal oxide semiconductor photoanodes. Monoclinic BiVO4 has a suitable band structure (Eg = 2.5 eV) and good stability, and has been proven to be a very efficient water oxidation photocatalyst. However, due to the short hole diffusion length of BiVO4 (70 nm), the poor separation efficiency of electron and hole pairs, and the slow reaction kinetics, its practical application in solar energy conversion is hindered. Therefore, it is urgent to design appropriate strategies to suppress the recombination of electron and hole pairs, improve the reaction kinetics, and thus improve the PEC water splitting performance.
[0005] As a semi-metal, bismuth has high carrier mobility and a narrow band gap. At the same time, it exhibits a surface plasmon resonance effect, which improves the PEC water splitting performance. Based on the powerful electron capture ability of metallic bismuth, there are currently a variety of in-situ reduction methods, such as Dennis YCLeung et al. of the University of Hong Kong prepared bismuth nanoparticles by light-assisted reduction of bismuth nitrate (Dennis YCLeung, et al. Appl. Catal. B: Environ., 2019, 258, 117954), and Zhang Fuqin et al. of Central South University prepared bismuth nanoparticles by hydrothermal treatment of bismuth vanadate (Fuqin Zhang, et al. J. Mater. Chem. A, 2023, 11, 20242), etc., but there are problems such as uneven particle size and large particle size. Laser technology has significant advantages due to its high energy density, wide adjustable energy density range and high monochromaticity, and can accurately output specific laser wavelengths. Using pulsed laser technology, uniform nanomaterials can be prepared quickly and directly, and their morphology and size can be precisely controlled. Summary of the invention
[0006] In order to solve the problems of poor separation efficiency of electron and hole pairs in bismuth vanadate photoanode, slow surface reaction kinetics, and uneven particle size of metal bismuth nanocluster, the present invention provides a laser induced in situ reduced metal bismuth nanocluster modified bismuth vanadate (Bi / BiVO4) composite photoanode, its preparation method and application, which exhibits excellent oxygen evolution activity and stability in the photoelectrochemical water decomposition process.
[0007] A method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode, the preparation method comprising the following steps:
[0008] Step 1, pre-treating the conductive substrate, ultrasonically washing the conductive substrate with deionized water, acetone, and ethanol, and treating the surface in an ozone atmosphere after drying to complete the pre-treatment.
[0009] Step 2, weigh a certain amount of potassium iodide and bismuth (III) nitrate pentahydrate, dissolve them in deionized water, stir until completely dissolved, and slowly drop concentrated nitric acid to adjust the pH to obtain a uniform mixed solution A.
[0010] Step 3, weigh a certain amount of p-benzoquinone and dissolve it in anhydrous ethanol, dissolve it by ultrasonic for half an hour to obtain a uniform mixed solution B, and slowly add the mixed solution B dropwise to the mixed solution A to obtain a precursor solution.
[0011] Step 4: In the precursor solution, BiOI nanoparticles are deposited on the pretreated conductive substrate by an electrodeposition method. After the deposition is completed, the conductive substrate is washed with deionized water and ethanol and dried to obtain a BiOI electrode.
[0012] Step 5, weigh a certain amount of vanadium acetylacetonate and ultrasonically dissolve it in a dimethyl sulfoxide solution to obtain a mixed solution C, take a certain amount of the mixed solution C and drop it on the BiOI electrode, bake it at high temperature in a muffle furnace, and after the electrode is cooled to room temperature, soak it in a NaOH solution to remove the vanadium pentoxide impurities remaining on the surface, then wash it with deionized water and ethanol and dry it to obtain a bismuth vanadate photoanode with a uniform surface.
[0013] Step 6, immersing the bismuth vanadate photoanode in a mixed solution of ethylene glycol and water, in situ inducing the reduction of bismuth vanadate to precipitate metallic bismuth nanoclusters under laser irradiation, and simultaneously inducing the generation of oxygen vacancies to prepare a Bi / BiVO4 composite photoanode.
[0014] Furthermore, in the step 1, the conductive substrate is fluorine-doped tin oxide conductive glass (FTO).
[0015] Furthermore, in step 2, the concentrations of potassium iodide and bismuth nitrate in the mixed solution A are 0.3-0.5 M and 0.03-0.05 M, respectively, and the pH is 1.7-1.8.
[0016] Furthermore, in step 3, the concentration of p-benzoquinone in the mixed solution B is 0.2-0.3 M; and the volume ratio of the mixed solution A to the mixed solution B is 5:3-5:1.
[0017] Furthermore, in step 4, a constant potential deposition method is used, the deposition potential is -0.1 V vs. Ag / AgCl reference electrode, and the deposition time is 150 to 200 s.
[0018] Furthermore, in the step 5, the concentration of vanadium acetylacetonate in the mixed solution C is 0.1 to 0.3 M, the amount of the mixed solution C added to the BiOI electrode with a working area of 1 cm×1 cm is 50 to 150 μL, the high-temperature calcination temperature is 400 to 500° C., the time is 120 minutes, the concentration of the NaOH solution is 1 M, and the immersion time is 20 to 40 minutes.
[0019] Furthermore, in step 6, the volume ratio of ethylene glycol to water is 1:1, the laser wavelength is 1064 nm, and the laser intensity is 150-350 mW cm -2 The irradiation time is 20 to 60 minutes.
[0020] A laser-induced in-situ reduced metal bismuth nanoclusters modified bismuth vanadate composite photoanode is prepared by the above-mentioned preparation method, and the surface of the bismuth vanadate composite photoanode is uniformly loaded with bismuth nanoclusters.
[0021] An application of a laser-induced in-situ reduced bismuth metal nanocluster modified bismuth vanadate composite photoanode for photoelectrocatalytic water decomposition to generate hydrogen and oxygen.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] (1) The present invention uses a laser-induced in-situ reduction method to induce the precipitation of metal bismuth nanoclusters on the surface of BiVO4 to form a bismuth vanadate composite photoanode modified by metal bismuth nanoclusters. Compared with the bismuth vanadate composite photoanode modified by metal bismuth nanoclusters prepared by other existing methods, the laser-induced in-situ reduction method is used to induce the precipitation of metal bismuth nanoclusters, which can prepare metal bismuth nanoclusters with uniform particle size, and tightly adhere to the surface of the bismuth vanadate photoelectrode, and increase the density of oxygen vacancies, significantly improve the photocurrent density, significantly increase the charge separation efficiency, and significantly inhibit the recombination of electron-hole pairs; the presence of bismuth nanoclusters induces the effective separation of electron-hole pairs, inhibits the recombination of bulk charge carriers, and significantly improves the PEC water splitting performance of BiVO4.
[0024] (2) The present invention utilizes simple electrodeposition and laser-induced in-situ reduction methods, has a simple synthesis process, good repeatability, and uses cheap and readily available materials, meeting environmentally friendly requirements.
[0025] (3) The present invention does not use any precious metals, which greatly reduces the cost and has important guiding significance for large-scale commercial applications in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The scanning electron microscope image and energy spectrum analysis diagram of the photoanode obtained in Example 2, wherein (a) is a scanning electron microscope image, (b) is a Bi element energy spectrum diagram, (c) is an O element energy spectrum diagram, and (d) is a V element energy spectrum diagram.
[0027] Figure 2 This is a transmission electron microscope image of the photoanode obtained in Example 2.
[0028] Figure 3 The photocurrent density curves of the photoanodes obtained in Example 2, Example 4 and Comparative Example 1, Comparative Example 2 are shown.
[0029] Figure 4 This is a graph of the charge transfer efficiency of the photoanodes obtained in Example 2, Example 4 and Comparative Example 1, Comparative Example 2.
[0030] Figure 5 The steady-state fluorescence spectra of the photoanodes obtained in Example 2, Example 4 and Comparative Example 1, Comparative Example 2. DETAILED DESCRIPTION
[0031] In order to further understand the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. At the same time, the examples described below are only a part of the present invention, not all. The following description is only to further illustrate the advantages and features of the present invention, rather than to limit the claims of the present invention. Other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.
[0032] The technical solution of the present invention will be further described below in conjunction with specific examples.
[0033] Example 1
[0034] A method for preparing a metal bismuth nanocluster modified bismuth vanadate composite photoanode comprises the following steps:
[0035] (1) Pretreatment of the conductive substrate: The conductive substrate is 1 cm×2 cm fluorine-doped tin oxide conductive glass. The conductive substrate is ultrasonically washed with deionized water, acetone, and ethanol for 30 minutes respectively. After drying, it is cleaned with a plasma cleaner in an ozone atmosphere for 30 minutes to complete the pretreatment.
[0036] (2) Weigh bismuth (III) nitrate pentahydrate and potassium iodide and dissolve them in 50 mL of deionized water. After stirring until completely dissolved, add concentrated nitric acid to adjust the pH to 1.7 to obtain a mixed solution A. The concentration of bismuth (III) nitrate pentahydrate in the mixed solution A is 0.03 M, and the concentration of potassium iodide is 0.3 M.
[0037] (3) p-Benzoquinone was weighed and dissolved in 20 mL of anhydrous ethanol, and ultrasonically treated for 30 minutes to obtain a mixed solution B, wherein the concentration of p-benzoquinone in the mixed solution B was 0.2 M. The mixed solution B was added dropwise to the mixed solution A, and the volume ratio of the mixed solution A to the mixed solution B was 5:1, to obtain a BiVO4 precursor BiOI solution.
[0038] (4) In 30 mL of precursor solution, BiOI nanoparticles were grown on a treated conductive substrate by electrodeposition, wherein the conductive substrate was used as a working electrode, Pt was used as a counter electrode, and a silver / silver chloride electrode was used as a reference electrode. Constant voltage deposition was performed using an applied bias of -0.1 V vs. Ag / AgCl electrode. The deposition time was about 150 seconds. After the deposition was completed, the BiOI electrode was washed with deionized water and ethanol and then dried to obtain a BiOI electrode with a uniform surface and a working area of 1 cm×1 cm.
[0039] (5) Vanadyl acetylacetonate was dissolved in about 5 mL of dimethyl sulfoxide solution and ultrasonically treated for 1 hour to obtain a mixed solution C, in which the concentration of vanadyl acetylacetonate was 0.1 M. 50 μL of the mixed solution C was dropped on the BiOI electrode, placed in a muffle furnace, and heated to 400 °C at a rate of 3 °C / min and maintained for 120 minutes. After cooling, it was immersed in a 1 M NaOH solution for 20 minutes to remove impurities remaining on the surface. The electrode was washed with deionized water and ethanol and dried to obtain a yellow BiVO4 electrode with a uniform surface.
[0040] (6) The BiVO4 photoanode was immersed in a mixed solution of ethylene glycol and water, with a volume ratio of ethylene glycol to water of 1:1. Under laser irradiation, bismuth vanadate was reduced and precipitated into metallic bismuth nanoclusters in situ. The laser wavelength was 1064 nm and the laser intensity was 150 mW / cm 2 , the laser irradiation time was 20 min, and the Bi / BiVO4 composite photoanode was prepared.
[0041] Example 2
[0042] A method for preparing a metal bismuth nanocluster modified bismuth vanadate composite photoanode comprises the following steps:
[0043] (1) Pretreatment of the conductive substrate: The conductive substrate is 1 cm×2 cm fluorine-doped tin oxide conductive glass. The conductive substrate is ultrasonically washed with deionized water, acetone, and ethanol for 30 minutes respectively. After drying, it is cleaned with a plasma cleaner in an ozone atmosphere for 30 minutes to complete the pretreatment.
[0044] (2) Weigh bismuth (III) nitrate pentahydrate and potassium iodide and dissolve them in 50 mL of deionized water. After stirring until completely dissolved, add concentrated nitric acid to adjust the pH to 1.75 to obtain a mixed solution A. The concentration of bismuth (III) nitrate pentahydrate in the mixed solution A is 0.04 M, and the concentration of potassium iodide is 0.4 M.
[0045] (3) Weigh p-benzoquinone and dissolve it in 20 mL of anhydrous ethanol, and perform ultrasonic treatment for 30 minutes to obtain a mixed solution B. The p-benzoquinone concentration in the mixed solution B is 0.23 M. The mixed solution B is added dropwise to the mixed solution A. The volume ratio of the mixed solution A to the mixed solution B is 5:2, and a BiVO4 precursor BiOI solution is obtained.
[0046] (4) In 30 mL of precursor solution, BiOI nanoparticles were grown on a treated conductive substrate by electrodeposition, wherein the conductive substrate was used as a working electrode, Pt was used as a counter electrode, and a silver / silver chloride electrode was used as a reference electrode. Constant voltage deposition was performed using an applied bias of -0.1 V vs. Ag / AgCl electrode. The deposition time was about 180 seconds. After the deposition was completed, the BiOI electrode was washed with deionized water and ethanol and then dried to obtain a BiOI electrode with a uniform surface and a working area of 1 cm×1 cm.
[0047] (5) Vanadyl acetylacetonate was dissolved in about 5 mL of dimethyl sulfoxide solution and ultrasonically treated for 1 hour to obtain a mixed solution C, in which the concentration of vanadyl acetylacetonate was 0.2 M. 100 μL of the mixed solution C was dropped on the BiOI electrode, placed in a muffle furnace, and heated to 450°C at a rate of 3°C / min and maintained for 120 minutes. After cooling, it was immersed in a 1 M NaOH solution for 30 minutes to remove impurities remaining on the surface, washed with deionized water and ethanol, and dried to obtain a yellow BiVO4 electrode with a uniform surface.
[0048] (6) The BiVO4 photoanode was immersed in a mixed solution of ethylene glycol and water, with the ratio of ethylene glycol to water being 1:1. Under laser irradiation, bismuth vanadate was reduced and precipitated into metallic bismuth nanoclusters in situ. The laser wavelength was 1064 nm and the laser intensity was 260 mW / cm 2 , the laser irradiation time was 40 min to prepare the Bi / BiVO4 composite photoanode.
[0049] Example 3
[0050] A method for preparing a metal bismuth nanocluster modified bismuth vanadate composite photoanode comprises the following steps:
[0051] (1) Pretreatment of the conductive substrate: The conductive substrate is 1 cm×2 cm fluorine-doped tin oxide conductive glass. The conductive substrate is ultrasonically washed with deionized water, acetone, and ethanol for 30 minutes respectively. After drying, it is cleaned with a plasma cleaner in an ozone atmosphere for 30 minutes to complete the pretreatment.
[0052] (2) Weigh bismuth (III) nitrate pentahydrate and potassium iodide and dissolve them in 50 mL of deionized water. After stirring until completely dissolved, add concentrated nitric acid to adjust the pH to 1.8 to obtain a mixed solution A, wherein the concentration of bismuth (III) nitrate pentahydrate is 0.05 M and the concentration of potassium iodide is 0.5 M.
[0053] (3) Weigh p-benzoquinone and dissolve it in 20 mL of anhydrous ethanol, and perform ultrasonic treatment for 30 minutes to obtain a mixed solution B. The p-benzoquinone concentration in the mixed solution B is 0.3 M. The mixed solution B is added dropwise to the mixed solution A. The volume ratio of the mixed solution A to the mixed solution B is 5:3, and a BiVO4 precursor BiOI solution is obtained.
[0054] (4) In 30 mL of precursor solution, BiOI nanoparticles were grown on a treated conductive substrate by electrodeposition, wherein the conductive substrate was used as a working electrode, Pt was used as a counter electrode, and a silver / silver chloride electrode was used as a reference electrode. Constant voltage deposition was performed using an applied bias of -0.1 V vs. Ag / AgCl electrode. The deposition time was about 200 seconds. After the deposition was completed, the BiOI electrode was washed with deionized water and ethanol and then dried to obtain a BiOI electrode with a uniform surface and a working area of 1 cm×1 cm.
[0055] (5) Vanadyl acetylacetonate was dissolved in about 5 mL of dimethyl sulfoxide solution and ultrasonically treated for 1 hour to obtain a mixed solution C, in which the concentration of vanadyl acetylacetonate was 0.3 M. 150 μL of the mixed solution C was dropped on the BiOI electrode, placed in a muffle furnace, and heated to 500°C at a rate of 3°C / min and maintained for 120 minutes. After cooling, it was immersed in a 1 M NaOH solution for 40 minutes to remove impurities remaining on the surface, washed with deionized water and ethanol, and dried to obtain a yellow BiVO4 electrode with a uniform surface.
[0056] (6) The BiVO4 photoanode was immersed in a mixed solution of ethylene glycol and water, with the ratio of ethylene glycol to water being 1:1. Under the irradiation of laser, the reduction of bismuth vanadate was induced in situ to precipitate metallic bismuth nanoclusters. The wavelength of the laser was 1064 nm and the intensity of the laser was 350 mW / cm 2 , the laser irradiation time was 60 min to prepare the Bi / BiVO4 composite photoanode.
[0057] Example 4
[0058] On the basis of the Bi / BiVO4 composite photoanode prepared in Example 2, the following steps are further performed:
[0059] (1) Co(OAc)2·4H2O and FeSO4·7H2O in a metal ratio of 4:1 were dissolved in 5 mL of N,N-dimethylformamide and labeled as solution A.
[0060] (2) 1 mmol of tetrabutylammonium bromide (Bu4BrN) and 0.3 mmol of 2,5-dihydroxy-1,4-benzoquinone (DHBQ) were dissolved in a mixed solution of 3 mL of ultrapure water, 3 mL of ethanol and 12 mL of DMF and stirred continuously under nitrogen for 30 minutes. The mixture was labeled as solution B.
[0061] (3) Solution A and solution B were mixed in a volume ratio of 5:18, and then the Bi / BiVO4 composite photoelectrode prepared in Example 2 was immersed in the mixed solution, heated at 110°C for 4 hours, washed with deionized water and ethanol three times, and dried at 60°C for 24 hours to obtain a CoFe / Bi / BiVO4 composite photoanode.
[0062] Comparative Example 1
[0063] The BiVO4 electrode was prepared by following the operation process of step (1) to step (5) in Example 2. A 10 mM Bi(NO3)3·5H2O aqueous solution was prepared and mixed with an ethylene glycol solution in a volume ratio of 1:1. The BiVO4 electrode was immersed in the solution. -2 The Bi / BiVO4 photoelectrode was prepared by light-assisted reduction under the irradiation of a xenon lamp for 60 minutes.
[0064] Comparative Example 2
[0065] Based on the Bi / BiVO4 composite photoanode prepared in Comparative Example 1, the following steps are further performed:
[0066] (1) Co(OAc)2·4H2O and FeSO4·7H2O in a metal ratio of 4:1 were dissolved in 5 mL of N,N-dimethylformamide and labeled as solution A.
[0067] (2) 1 mmol of tetrabutylammonium bromide (Bu4BrN) and 0.3 mmol of 2,5-dihydroxy-1,4-benzoquinone (DHBQ) were dissolved in a mixed solution of 3 mL of ultrapure water, 3 mL of ethanol and 12 mL of DMF and stirred continuously under nitrogen for 30 minutes. The mixture was labeled as solution B.
[0068] (3) Solution A and solution B were mixed in a volume ratio of 5:18, and then the Bi / BiVO4 composite photoelectrode prepared in Comparative Example 1 was immersed in the mixed solution, heated at 110°C for 4 hours, washed with deionized water and ethanol three times, and dried at 60°C for 24 hours to obtain a CoFe / Bi / BiVO4 composite photoanode.
[0069] Figure 1 The scanning electron microscope image and energy spectrum diagram of the Bi / BiVO4 photoanode in Example 2 show that the BiVO4 nanostructure photoelectrode was successfully synthesized on a conductive substrate in Example 2, and the metal bismuth nanoclusters did not change the morphology of BiVO4 during the precipitation process. Due to the small size of the metal bismuth nanoparticles, no bismuth nanoclusters were seen in the scanning electron microscope image.
[0070] Figure 2This is a transmission electron microscope image of the Bi / BiVO4 photoanode in Example 2. The laser-induced in-situ reduction method successfully induced the uniform precipitation of metal bismuth nanoclusters on the BiVO4 surface.
[0071] The photocurrent density of different photoanodes in Example 2, Example 4, Comparative Example 1 and Comparative Example 2 was measured by linear sweep voltammetry, and the charge transfer efficiency of each photoelectrode was measured using sodium sulfite as a hole sacrificial agent. The results are as follows:
[0072] Figure 3 The linear scanning voltammetry curves of the photoelectrodes prepared in Example 2, Example 4 and Comparative Example 1 and Comparative Example 2 show that the photocurrent density of the Bi / BiVO4 photoelectrode prepared in Comparative Example 1 is significantly smaller than that of the Bi / BiVO4 photoelectrode prepared by laser-induced in-situ reduction in Example 2, which is attributed to the more uniformly dispersed and smaller particle size metal bismuth nanoclusters. After the growth of the CoFe catalyst, the CoFe / Bi / BiVO4 photoanode prepared in Example 4 achieved 6.07 mA cm at 1.23 V vs. RHE. -2 The photocurrent density is higher than that of the photoelectrode prepared in Comparative Example 2, indicating that there is a better synergistic effect between the bismuth nanoclusters prepared by laser-induced in-situ reduction and the co-catalyst.
[0073] Figure 4 The charge transfer efficiency diagrams of Example 2, Example 4 and Comparative Example 1 and Comparative Example 2 show that the photoanodes prepared in Example 2 and Example 4 have higher charge transfer efficiency than those prepared in Comparative Example 1 and Comparative Example 2. This indicates that the metal bismuth nanoclusters, as charge transfer media, effectively promote the transfer of holes from the bismuth vanadate substrate to the surface of the co-catalyst.
[0074] The steady-state fluorescence spectra of the photoelectrodes of Example 2, Example 4 and Comparative Example 1, Comparative Example 2 were measured using a FluoroMax-4P steady-state transient fluorescence spectrometer. Figure 5 The steady-state fluorescence spectra of the four show that the charge recombination of the Bi / BiVO4 photoanode prepared in Example 2 is significantly reduced compared with that in Comparative Example 1, and the modification of the CoFe / Bi / BiVO4 photoanode metal bismuth nanoclusters and the loading of CoFe in Example 4 greatly reduce the electron-hole pair recombination rate of the photoanode, which once again proves that the metal bismuth nanoclusters as charge transfer media promote the separation and transmission of charges and inhibit the recombination of charges, thus exhibiting excellent photoelectrochemical performance.
[0075] The above-mentioned embodiments only express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode, characterized in that: The preparation method firstly deposits BiOI nanoparticles on a conductive substrate by electrodeposition to obtain a BiOI electrode; secondly, introduces vanadium by high-temperature calcination to generate a bismuth vanadate nanostructure photoanode; finally, in situ precipitates metal bismuth nanoclusters on bismuth vanadate by laser-induced in-situ synthesis to prepare a bismuth nanocluster-modified bismuth vanadate composite photoanode.
2. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, pre-treating the conductive substrate; Step 2, dissolving potassium iodide and bismuth (III) nitrate pentahydrate in deionized water, stirring until completely dissolved, and then dropping concentrated nitric acid to adjust the pH to obtain a mixed solution A; Step 3, dissolving p-benzoquinone in anhydrous ethanol to obtain a uniform mixed solution B, and adding the mixed solution B dropwise to the mixed solution A to obtain a precursor solution; Step 4, depositing BiOI nanoparticles on the pretreated conductive substrate by electrodeposition in the precursor solution, washing and drying after the deposition, to obtain a BiOI electrode; Step 5, dissolving vanadium acetylacetonate in a dimethyl sulfoxide solution to obtain a mixed solution C, dropping the mixed solution C on a BiOI electrode, calcining at high temperature in a muffle furnace, and soaking the electrode in a NaOH solution to remove surface impurities after the electrode is cooled to room temperature, followed by washing and drying to obtain a bismuth vanadate photoanode; Step 6, immersing the bismuth vanadate photoanode in a mixed solution of ethylene glycol and water, in situ inducing bismuth vanadate reduction under laser irradiation to precipitate metallic bismuth nanoclusters, and preparing a bismuth vanadate composite photoanode, namely, a Bi / BiVO4 composite photoanode.
3. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 2, characterized in that: In the step 1, the conductive substrate is made of fluorine-doped tin oxide conductive glass.
4. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 1, characterized in that: In the step 2, the concentrations of potassium iodide and bismuth nitrate in the mixed solution A are 0.3-0.5M and 0.03-0.05M respectively, and the pH is 1.7-1.
8.
5. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 1, characterized in that: In the step 3, the concentration of p-benzoquinone in the mixed solution B is 0.2-0.3 M; the volume ratio of the mixed solution A to the mixed solution B is 5:3-5:
1.
6. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 1, characterized in that: In step 4, the deposition potential is -0.1V vs. Ag / AgCl reference electrode, and the deposition time is 150 to 200 seconds.
7. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 1, characterized in that: In the step 5, the concentration of vanadyl acetylacetonate in the mixed solution C is 0.1-0.3M, the amount of the mixed solution C added to each 1cm×1cm working area of the BiOI electrode is 50-150μL, the high temperature calcination temperature is 400-500°C, and the time is 120 minutes.
8. The method for preparing a laser-induced in-situ reduced bismuth metal nanocluster-modified bismuth vanadate composite photoanode according to claim 1, characterized in that: In step 6, the laser wavelength is 1064nm and the laser intensity is 150-350mWcm -2 The irradiation time is 20 to 60 minutes.
9. A laser-induced in-situ reduced bismuth metal nanocluster modified bismuth vanadate composite photoanode, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The surface of the bismuth vanadate composite photoanode is uniformly loaded with bismuth nanoclusters.
10. The use of a laser-induced in-situ reduced bismuth metal nanoclusters modified bismuth vanadate composite photoanode according to claim 9, characterized in that: Applied to photoelectrocatalytic water decomposition to generate hydrogen and oxygen.